Legal Challenges of Swarm Intelligence Exploitation in Cybercrime across Distributed Systems - AllahRakha, Naeem (Lembaga Contrarius Indonesia, 2026)
Cybercrime continues to evolve at a pace that challenges the adaptability of existing legal frameworks, particularly with the emergence of swarm intelligence as a tool for coordinating autonomous and distributed cyberattacks. This study aims to analyse the adequacy of contemporary international cybercrime law in addressing the exploitation of swarm intelligence, with specific reference to recent global regulatory developments. The research employs a doctrinal legal method, combining normative analysis of treaty provisions with a qualitative review of recent enforcement practices. The findings reveal four principal deficiencies: the ambiguity of legal liability in decentralized systems lacking identifiable control; jurisdictional fragmentation that enables regulatory evasion; inherent limitations in detecting multi-agent coordinated attacks; and a structural mismatch between legal norms and states’ technical enforcement capacities. These gaps demonstrate that existing frameworks remain insufficient to respond effectively to technologically sophisticated cyber threats. The study concludes that without targeted legal reform, including the development of specialized regulatory instruments, enhanced international cooperation mechanisms, and improved technical capacity, the enforcement of cybercrime law will remain reactive and fragmented. Strengthening the integration between legal doctrine and technological realities is therefore essential to ensure effective governance and protection in the evolving digital landscape.